Shale lithofacies mechanical differences from tectonic-diagenetic coupling and their response to hydraulic fracture network propagation - Yang, Liyan; Peng, Xiangdong; Hu, Ying; Liu, Anan (Frontiers in Earth Science, 2025)
Fracture propagation modes in shale formations exhibit significant variations across different lithofacies during tectonic deformation and hydraulic fracturing. Understanding how the mechanical properties of these lithofacies influence fracture network development is crucial for effective shale reservoir stimulation. This study investigates the organic-rich Wufeng–Longmaxi Formation shale in the southern Sichuan Basin. Lithofacies were classified, and their mechanical properties analyzed, focusing on stress–strain behavior and energy accumulation/release characteristics under varying stress conditions. The study also examines the fracturing behavior of single and stacked lithofacies combinations. The findings reveal five primary lithofacies in the Lower Longmaxi (Long-1) submember of the study area. Under uniaxial compression, samples from different lithofacies predominantly fail through tensile splitting, exhibiting linear elastic energy accumulation and vertical splitting fractures. Under triaxial compression, the elastic deformation phase shortens, with increased energy dissipation during plastic deformation; shear fractures become the dominant failure mode. Among the lithofacies, siliceous shale exhibits the largest stress drop and highest ratio of released elastic energy, leading to the most intense failure. Due to its brittleness, siliceous shale undergoes planar fracture propagation in stress-unloading zones. Laminated calcareous–siliceous shale demonstrates fracture propagation capacity second only to siliceous shale, while clay-rich siliceous shale shows the weakest fracture development. Hydraulic fracturing in a stacked sequence of thinly laminated siliceous shale and clay-rich siliceous shale is significantly influenced by bedding planes acting as “stress barriers.” Fractures propagating upward exhibit stepped, staircase-like growth and branching, forming a complex fracture network characterized by short fracture segments, numerous branches, complex morphologies, and strong lateral connectivity. In contrast, combinations of massive siliceous shale and massive clay-rich siliceous shale (with minimal bedding) facilitate vertical stress transmission, resulting in simpler fractures that are fewer in number, longer, and more planar. These insights provide valuable guidance for identifying sweet spots and optimizing stimulation strategies in shale formations with varying lithofacies combinations.